M-2-7m+2=-18

Simple and best practice solution for M-2-7m+2=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for M-2-7m+2=-18 equation:


Simplifying
M + -2 + -7m + 2 = -18

Reorder the terms:
-2 + 2 + M + -7m = -18

Combine like terms: -2 + 2 = 0
0 + M + -7m = -18
M + -7m = -18

Solving
M + -7m = -18

Solving for variable 'M'.

Move all terms containing M to the left, all other terms to the right.

Add '7m' to each side of the equation.
M + -7m + 7m = -18 + 7m

Combine like terms: -7m + 7m = 0
M + 0 = -18 + 7m
M = -18 + 7m

Simplifying
M = -18 + 7m

See similar equations:

| -2.5x=.25 | | 2/5(25)-8=-1/5(25)+7 | | -9x+15=22-4(x+12) | | x^4+-5x^3+-3x^2=0 | | -2(-3m-8)+7m=94 | | 8x-8y=8 | | 7y-7-4y+6=0 | | y+15=-3y-9 | | qx+rx=s | | N-10+5n+6=32 | | 182x-0.02x^2+18000=0 | | 44-10n=6(-3n+2) | | 6+3y=15 | | 24=4*w*2 | | -10+8p+1+10p=9 | | -t*6=-7*8 | | (b+9)(b-12)=0 | | 5t+5=7t-4 | | -4-7+1= | | 6x^2-30x+11=0 | | -287=7(1+7n) | | 5y-2(y-6)=43 | | 24=4*w*3 | | -2=6a-4 | | 12x-7=24x+2 | | 2*56=-4 | | 2/5(25)-8=1/5(25)+7 | | 120w-23w=691 | | 1.25-0.3k+.5=1.3+0.5k | | 12x=11x-23 | | P-4+6+7p=74 | | 120w+23w=691 |

Equations solver categories